E-Arbitration: Digitization Of Business Dispute Resolution Pada Sektor E-Commerce Dalam Menyongsong Era Industri 4.0 Di Tengah Pandemi Covid-19 - Juan Matheus (Universitas Islam Indonesia, 2021)
The occurrence of the Covid-19 pandemic forced the Government of Indonesia to establish a policy of social restrictions to reduce the rate of transmission of Covid-19. This resulted in BANI stopping the trial, causing delays in the dispute resolution process. To overcome this, a new innovation is needed in the form of online arbitration or E-Arbitration. This study aims to examine the problems, first, how to regulate E-Arbitration as an alternative to e-commerce dispute resolution? Second, can E-Arbitration be implemented in the midst of the Covid-19 Pandemic? This research is a type of normative juridical research using a statutory approach, a conceptual approach, and a comparative approach. From the results of the study, it was concluded, firstly, the application of E-Arbitration is not explicitly regulated in the legislation and is only based on Decree Number 20.015/V.SK-BANI/HU concerning Regulations and Procedures for the Implementation of Electronic Arbitration (Electronic Arbitration Decree). Second, the implementation of E-Arbitration in the midst of the Covid-19 Pandemic can still be carried out by taking into account the decree and other regulations. In addition, special regulations are needed that regulate E-Arbitration in order to open new alternatives in resolving e-commerce disputes. Keywords: Business dispute resolution; e-arbitration; e-commerceAbstrakTerjadinya Pandemi Covid-19 memaksa Pemerintah Indonesia menetapkan kebijakan pembatasan sosial untuk menekan laju penularan Covid-19. Hal ini berdampak pada BANI yang menghentikan persidangan sehingga menyebabkan terhambatnya proses penyelesaian sengketa. Guna mengatasi hal tersebut diperlukan sebuah inovasi baru berupa arbitrase online atau E-Arbitration. Penelitian ini bertujuan untuk mengkaji permasalahan, pertama, bagaimana pengaturan E-Arbitration sebagai alternatif penyelesaian sengketa e-commerce? Kedua, apakah E-Arbitration dapat diterapkan di tengah Pandemi Covid-19. Penelitian ini merupakan jenis penelitian yuridis normatif dengan menggunakan pendekatan perundang-undangan, pendekatan konseptual, dan pendekatan komparatif. Dari hasil penelitian disimpulkan, pertama, penerapan E-Arbitration tidak diatur secara tegas dalam peraturan perundang-undangan dan hanya berdasarkan Surat Keputusan Nomor 20.015/V.SK-BANI/HU tentang Peraturan dan Tata Cara Penyelenggaraan Arbitrase Elektronik (SK Arbitrase Elektronik). Kedua, pelaksanaan E-Arbitration di tengah Pandemi Covid-19 tetap dapat dilakukan dengan memperhatikan surat keputusan tersebut dan peraturan lainnya. Selain itu, diperlukan peraturan khusus yang mengatur E-Arbitration agar dapat membuka alternatif baru dalam menyelesaikan sengketa e-commerce.Kata Kunci: E-Arbitration; penyelesaian sengketa bisnis; e-commerce